Control Sequence Ranking for Critical System Based on Health of Equipment Thanks to Choquet Integral - Bouaziz, Mohammed-Farouk; Marange, Pascale; Voisin, Alexandre; Petin, Jean-Francois (Frontiers in Artificial Intelligence, 2021)
This paper presents a ranking method of operating sequences based on the actual condition of complex systems. This objective is achieved using the health checkup concept and the multi-attribute utility theory. Our contribution is the proposal of sequences ranking process using data and experts’ judgments. The ranking results in a decision making element; it allows experts to have an objective and consensual ranking to be used for decision making. A case study is presented based on an experimental platform; it allows us to compare two aggregation operators: the weighted mean and the Choquet integral.